PENGARUH MEDIA SIKAKIMI (SILANG KATA KIMIA) TERHADAP HASIL BELAJAR SISWA PADA MATERI STRUKTUR ATOM DI KELAS X IPA MAN 1 PONTIANAK - Rahmayana, Yeni; Enawaty, Eni; Hadi, Lukman (Jurnal Kajian Pembelajaran dan Keilmuan, 2021)
ABSTRACTÂ This study aims to determine where there is as significant difference achievement between those who are tought using Sikakimi Media and without between those who are tought using Sikakimi Media who are the topic structure material and to determine the effect size of Sikakimi an students achievement. To achievement the aims, a quasy experimental design was conducted to classes from populations which consists of four classes where choosen as samples though ramdom sampling technique. The sample were X IPA 1 class as experimental group and X IPA 3 as control group. Acoording to research design, with classes were given a set of test before and after treatment. To achieve the first aim, data tested using U-Man Whitney test and to achieve the second data tested using glass test. Acoording to U-Man Whitney data analysis, probality velue was 0,001 which meant there was a significant difference in achievement between both classes. Acoording to glasses test, the effect size score was 0,76 which mean Sikakimi had 27,64% in the medium category.Â Keywords: Media, Sikakimi, Structure Material